Differences in the Use of Covid-19 Comorbid Drugs in Before and Early Of Pandemic - Oskar Skarayadi; Syarifuddin; M.Robby Ramdhani; M Rifky Rohman; Arif R Sjahidy (Institute of Computer Science (IOCS), 2022)
Comorbid patients with Covid 19 affect the severity of the infection. This study aims to examine the utilization of generic medications in the treatment of comorbid Covid-19. Data were retrieved retrospectively from Al Ihsan Hospital's medical records. The data summarize the use of generic medicines for comorbid Covid-19 in the year preceding and in the first year of the pandemic. Metformin is the most commonly recommended medication for type 2 diabetes management.In contrast, Acarbose was the most extensively used medicine before the epidemic. Pioglitazone is the least prescribed diabetes medication. Before the pandemic, Amlodipine 10 mg was the most commonly prescribed medication for cardiovascular disease management. This is distinct from the pre-pandemic period when Ramipril was the most frequently used medication. Verapamil was the least prescribed medication prior to and throughout the epidemic. Three of the eleven medicine names analyzed in the Diabetes Comorbid group indicated that there was a significant variation in use between before and during the pandemic. Thirteen of the twenty-one medicine names analyzed in the Cardiovascular Comorbid group showed a substantial variation in usage between before and during a pandemic.